1990
DOI: 10.1073/pnas.87.17.6748
|View full text |Cite
|
Sign up to set email alerts
|

Metal-ion-center assembly of ferredoxin and plastocyanin in isolated chloroplasts.

Abstract: Most chloroplastic proteins are cytosolically synthesized and posttranslationally transported to their proper locations.' Two examples of this group of proteins are ferredoxin and plastocyanin, both of which are metal-containing components of the photosynthetic electron-transport chain.The import process for these two proteins includes the insertion of the metal ions to produce the holo forms of the proteins. We show here that in vitro translated precursor. proteins of ferredoxin and plastocyanm are synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 25 publications
4
47
0
Order By: Relevance
“…By contrast, holoplastocyanin was barely detectable in paa1-1 and paa1-3, and apoplastocyanin accumulated instead ( Figure 8A, untreated). Treatment with ascorbate and KCN, which converts holoplastocyanin to forms of apoplastocyanin with different electrophoretic mobilities on native gels (Li et al, 1990), indicated that the wild-type plants had much higher contents of plastocyanin polypeptides ( Figure 8A, ascorbate/KCN treated), a finding that was confirmed by denaturing SDS-PAGE ( Figure 8B). This difference was not apparent in the untreated samples separated on the native gel ( Figure 8A, untreated), presumably because the anti-plastocyanin antibody detected apoplastocyanin much more efficiently than holoplastocyanin.…”
Section: Paa1 Function Is Required For Holoplastocyanin Formationsupporting
confidence: 52%
See 2 more Smart Citations
“…By contrast, holoplastocyanin was barely detectable in paa1-1 and paa1-3, and apoplastocyanin accumulated instead ( Figure 8A, untreated). Treatment with ascorbate and KCN, which converts holoplastocyanin to forms of apoplastocyanin with different electrophoretic mobilities on native gels (Li et al, 1990), indicated that the wild-type plants had much higher contents of plastocyanin polypeptides ( Figure 8A, ascorbate/KCN treated), a finding that was confirmed by denaturing SDS-PAGE ( Figure 8B). This difference was not apparent in the untreated samples separated on the native gel ( Figure 8A, untreated), presumably because the anti-plastocyanin antibody detected apoplastocyanin much more efficiently than holoplastocyanin.…”
Section: Paa1 Function Is Required For Holoplastocyanin Formationsupporting
confidence: 52%
“…might be explained by a lack of functional plastocyanin. To assess this possibility, thylakoid lumen proteins from wild-type and paa1 plants were subjected to native gel electrophoresis (Li et al, 1990) to separate holoplastocyanin (containing Cu) and apoplastocyanin (lacking Cu). In wild-type plants, plastocyanin was present predominantly in the holo form ( Figure 8A, untreated).…”
Section: Paa1 Function Is Required For Holoplastocyanin Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the copper-requiring step in the biosynthesis of plastocyanin (i.e. formation of a stable holoprotein) is compartmentalized in the lumen of the thylakoid membrane (15,18), we cannot definitively conclude that partitioning of copper between the regulator (in the cytosol or nucleus) and plastocyanin (in the lumen) is set by their own relative cellular stoichiometries and affinities for copper. Distribution of copper between the regulator and plastocyanin might, for example, be determined by the affinities and directionalities of intracellular copper-transporting systems.…”
Section: Plastocyanin Content Affects the Sensory Threshold For The Cmentioning
confidence: 98%
“…The importance of Fe-S clusters for photosynthesis stimulated early studies in the assembly of these metal cofactors in chloroplasts using nuclear-encoded, imported ferredoxin as a model protein (Takahashi et al 1986;Li et al 1990). By adding 35 S-labeled cysteine to lysed spinach chloroplasts, it was shown that cysteine is the source of sulfur for the ½2Fe-2S cluster of ferre-doxin (Takahashi et al 1991b).…”
mentioning
confidence: 99%